Epidemiology survey on the prevalence of infections intestinal parasitesin of Working in restaurants and food shope in the province of diwaniyah - Safaa Racine (Al-Qadisiyah Journal of Pure Science, 2017)
This study was eonducted in order to findout the prevalence of intestinal parasites infectious In working in restaurants and stores food and learn more kinds of protozoan wide spread Included collecting 220 stool samples from people adults aged 15-45 years were separated Sample collectin stage and stage.and divided in to phases in summer ,for three months ,june- July –August ,and the same rate of 110 stage of winter is December Junuary –February ,and By 110 the same study showed parasitic infection rate (Entamoeba ,Giardia ,cyclospora ,Blastocystis ) %12.2 the ratiostood at these parasites in the summer %13.6 either in the Was recorded %10.9 .either in junuary rates in all parasites were recorded Entamoeba %5.9 in winter and summer while Giardia appear rate %3.1 while Cyclospora rate in %2.2While Blasto cystis was the lowest rate it %o.9 .Tuse , these percentages show the seriousness of non medical examination and the presence Of medical leave for workers in the field of food and it s preparation from the medical and economic importance in the transmiss of disease